CHONDROSARCOMA IN THE XXI CENTURY - Vyrva, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Chondrosarcoma (CHS) is a rare oncopathology, is the third most common primary bone tumor after multiple myeloma and osteosarcoma. It accounts for about 25 % of the total number of bone sarcomas. CHS mainly affects adults and occurs more often in people older than 40 years, in children and adolescents it is less than 5 % of all cases of primary CHS. The most common CHS sites can be any bone containing cartilage, but most often this tumor is found in pelvis, femur and shoulder bones, and ribs. CHS are divided: by origin (primary and secondary), anatomical site (central — inside the bone marrow canal, peripheral — inside the existing osteochondroma, periosteal — on the bone surface), histological degrees GI-GII-GIII. The WHO classification (2020) includes central normal, secondary peripheral, periosteal, dedifferentiated, mesenchymal and clear-cell CHS. More than 90 % of conventional CHS are tumors of low and medium malignancy degree, with a low potential for metastasis. CHS is caused by mutations in genes that control bone growth and development. The main risk factors are the patientʼs age, previous radiation, genetic factors and predisposition to oncological diseases. Diagnosis of CHS is based on a complex algorithm, which involves collecting the patient’s complaints, anamnesis, clarifying clinical symptoms, imaging (X-ray, CT, MRI), histopathological picture. The biopsy conclusion is the most important in establishing the final diagnosis. However, there are several tumors whose histological picture is similar to CHS: enchondroma, chondroblastoma, osteosarcoma, giant cell tumor of bone, dedifferentiated liposarcoma, synovial sarcoma. The CHS treatment protocol is determined based on the results of anamnestic data, imaging, histopathological results, CHS classification, and its final tumor subtype. The «gold standard» remains surgical removal of the tumor. Radiation and chemotherapy don’t play a significant role in the treatment of CHS, but require further study. Targeted and immunotherapy have a certain potential, even with a high degree of CHS resistance to traditional chemotherapy.